Binary bent sequences of order 64 - Chang, Derek K. (Utilitas Mathematica, 1997)
We show in this paper that the number of binary bent sequences of order 64 is 5,425,430,528. Since it is known that there are only 37,879,808 bent-based and 10,321,920 linear-based binary bent sequences of order 64, we see that most of the binary bent sequences of order 64 are neither bent-based nor linear-based. This disproves a recent conjecture of C.M. Adams and S.E. Tavares on the structure of bent sequences.